Challenges and Traditions: Exploring the Concept of Pamali In Lakkang Island Society, Makassar - Yulianandaris, Yulianandaris; Mas Dadang Enjat Munajat; Yustikasari; Evi Novianti; Anees Janee Ali (Politeknik Pariwisata Lombok, 2025)
Introduction: Lakkang Island is famous for its beautiful scenery and rich culture that attracts the attention of tourists because of its dynamic tradition, namely Pamali or Kasimpalli which has been passed down from generation to generation. However, the increasing popularity of the island as a tourist destination and the presence of immigrant communities present challenges in preserving this tradition. This study analyzes the impact of tourism on Lakkang culture and explores the adaptation between local communities and immigrants in maintaining socio-cultural harmony.Methodology: This study uses a qualitative descriptive approach to explore the concept of Pamali through interviews, observations, and documentation. The informants included traditional leaders and the people of Lakkang Island, such as the leader of the Sampara Traditional Council Daeng Nampa and Subarka immigrants. Data was collected from January to May 2023.Findings: Tourism and immigration affect the preservation of the cultural heritage of Lakkang Island. Despite the pressure, the Pamali tradition remains the cornerstone of local identity. This study shows how local communities and immigrants face and adapt to these challenges which makes Pamali a key factor in upholding cultural practices and fostering community harmony in the midst of socio-cultural changes.Conclusion: Pamali's presence on Lakkang Island reflects a strong adherence to traditional values that play an important role in maintaining the island's cultural identity. The importance of Pamali in balancing tradition with modern demands, thus ensuring that the unique cultural heritage of Lakkang Island remains sustainable for future generations.